Intimate partner violence and abuse: a qualitative exploration of UK military personnel and civilian partner experiences - Lane, Rebecca (Journal of family violence, 2024)
Purpose: The prevalence of Intimate Partner Violence and Abuse (IPVA) perpetration and victimisation has been found to be higher in serving and ex-serving military samples compared to civilians. Despite this, there is a lack of qualitative research exploring the IPVA experiences of couples in which one or both partners are serving or have served in the military. This qualitative study aimed to explore IPVA experiences within the UK military community from the perspective of serving and ex-serving military personnel and civilian partners of UK military personnel. Method: One-to-one telephone interviews were conducted with 40 serving and ex-serving military personnel (29 male, 11 female) and 25 female civilian partners. Data was analysed using thematic analysis. Results: Four superordinate themes were derived: (1) patterns and directions of IPVA, (2) types of IPVA, (3) perceived drivers of IPVA and (4) perceived impact of IPVA. The findings point to frequent bidirectional abuse in part driven by poor communication and emotion regulation, whilst also highlighting the experiences of severe IPVA victimisation of civilian partners by military personnel motivated by power and control. Perceived drivers of both IPVA perpetration and victimisation include military factors borne of military culture or training, alcohol and mental health difficulties. Conclusion: These results highlight the role of cultural norms, as well as the role of emotion dysregulation, poor communication skills and mental health difficulties in explaining and perpetuating abuse within ecological theoretical frameworks of violence among couples within which one or both partners are serving or ex-serving military personnel.